Comparison of Phosphor Removal Efficiency of Rain Treatment Materials Containing Illite - Kim, Yootaek; Chae, Taesung (International Journal of Engineering and Technology, 2018)
Artificial lakes constitute more than 40% of drinking water sources, and can be easily eutrophicated by accumulation of phosphor, nitrogen, and nutrition salts introduced by various industrial and domestic origins after 10â€“30 years of their construction. Specifically, the concentration of phosphor is considered as an important factor that influences eutrophication, and causes seven times the eutrophication of nitrogen. In the present study, porous ceramics were fabricated with bottom ashes (BA) from power plants for recycling purposes and illite, which is known to be an efficient absorption material for phosphor in water. The phosphor removal efficiency reached up to 59% when the composition rate of illite to BA was 4 to 6. The study indicates the possibility of developing phosphor absorbing porous ceramics by using spent materials such as BA as substitutes for expensive illite without a significant decrease in phosphor removal efficiency.Â Â